Pathogenic mechanisms and therapeutic approaches for the tauopathies - Duff, Karen (Henry Stewart Talks, 2010)
Tauopathies, Alzheimer's Disease and frontal temporal lobe dementia, Pathogenic mechanisms, Therapeutic approaches for the tauopathies